2020
DOI: 10.3847/1538-4357/aba532
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Spectroscopic Monitoring Observations of FU Orionis–type Object, V960 Mon

Abstract: We present the results of high-resolution (R ≥ 30,000) optical and near-infrared spectroscopic monitoring observations of a FU Orionis-type object, V960 Mon, which underwent an outburst in 2014 November. We have monitored this object with the Bohyunsan Optical Echelle Spectrograph (BOES) and the Immersion GRating INfrared Spectrograph (IGRINS) since 2014 December. Various features produced by a wind, disk, and outflow/jet were detected. The wind features varied over time and continually weakened after the outb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 70 publications
3
20
0
Order By: Relevance
“…We also detected several forbidden emission lines: (Magakian et al 2013;Takagi et al 2018;Kóspál et al 2020;Park et al 2020). In contrast, these lines are generally found in classical T Tauri stars as tracers of outflow or jets (Cabrit et al 1990;Hartmann 2009).…”
Section: Optical Spectroscopymentioning
confidence: 77%
“…We also detected several forbidden emission lines: (Magakian et al 2013;Takagi et al 2018;Kóspál et al 2020;Park et al 2020). In contrast, these lines are generally found in classical T Tauri stars as tracers of outflow or jets (Cabrit et al 1990;Hartmann 2009).…”
Section: Optical Spectroscopymentioning
confidence: 77%
“…Only V346 Nor shows several H 2 emission lines similar to V899 Mon. The H 2 2.122 µm emission line was detected in the FUor V960 Mon (Park et al 2020) and in some EXors (Kóspál et al 2011a;Hodapp et al 2019Hodapp et al , 2020, however, none of the other H 2 transitions were detected.…”
Section: Molecular Hydrogen Linesmentioning
confidence: 91%
“…Na I 2.2062 µm line is blended by Si I 2.2069 µm line; therefore, we did not measure the HWHD of this line. A general trend of HWHD decreases with increasing wavelength, suggesting that these atomic lines are formed at the disk (Zhu et al 2009;Lee et al 2015;Park et al 2020).…”
Section: Permitted Atomic Linesmentioning
confidence: 96%
“…In order to estimate the rotational velocity (vsini), we convolved the stellar spectrum with a Gaussian profile to account for the rotational broadening of the lines and compared their spectra to V1515 Cyg. For this analysis, we adopted the standard stellar spectra from F8 to G8 supergiants used in Park et al (2020), which are observed with the same observing setup as V1515 Cyg. First, we averaged four spectral lines (Fe I 6141.7, Fe I 6411.6, Ca I 6439.1, and Fe I 7511.0 Å) by normalizing each peak intensity for V1515 Cyg and standard stars.…”
Section: Optical Spectroscopymentioning
confidence: 99%